2005
DOI: 10.5194/angeo-23-1849-2005
|View full text |Cite
|
Sign up to set email alerts
|

First current density measurements in the ring current region using simultaneous multi-spacecraft CLUSTER-FGM data

Abstract: Abstract. The inner magnetosphere's current mapping is one of the key elements for current loop closure inside the entire magnetosphere. A method for directly computing the current is the multi-spacecraft curlometer technique, which is based on the application of Maxwell-Ampère's law. This requires the use of four-point magnetic field high resolution measurements. The FGM experiment on board the four Cluster spacecraft allows, for the first time, an instantaneous calculation of the magnetic field gradients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
112
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 28 publications
10
112
1
Order By: Relevance
“…5a, we can confirm that the average magnitudes of the measured current density at the Cluster ring plane crossing (∼4-4.5 R E ) ranged from 9 to 27 nA m −2 , which are greater than the quiet time averages of ∼1-4 nA m −2 derived using the Parker equation from observed magnetic field and particle pressures (but then estimated over the range of L-values 2-9; see Lui andHamilton, 1992, andDe Michelis et al, 1999). This difference has been accounted for by Vallat et al (2005) who also used the Curlometer technique, deriving similar values of 30 nA m −2 to our study. The profile of |J | also confirms that there is an enhancement in the morning sector and a dip in after noon.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…5a, we can confirm that the average magnitudes of the measured current density at the Cluster ring plane crossing (∼4-4.5 R E ) ranged from 9 to 27 nA m −2 , which are greater than the quiet time averages of ∼1-4 nA m −2 derived using the Parker equation from observed magnetic field and particle pressures (but then estimated over the range of L-values 2-9; see Lui andHamilton, 1992, andDe Michelis et al, 1999). This difference has been accounted for by Vallat et al (2005) who also used the Curlometer technique, deriving similar values of 30 nA m −2 to our study. The profile of |J | also confirms that there is an enhancement in the morning sector and a dip in after noon.…”
Section: Discussionsupporting
confidence: 50%
“…Their study was limited by the data taken during 2002, but suggested that the ring current can extend from −65 to 65 • in latitude all over the evening and postmidnight sectors about 9 h of MLT. The present paper extends the study of Vallat et al (2005) to survey the distributions of the ring current at all MLT and discuss the locations of the connecting region 2 field-aligned currents (FACs). Figure 1 shows an example orbit of the Cluster spacecraft S/C1 between 05:00 and 18:00 UT on 6 February 2004.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations